Abatement characteristics of N2O in low-pressure plasma reactor. (14th December 2015) - Hur, M; Lee, J O; Lee, J Y; Kang, W S; Song, Y-H
Abstract: The abatement characteristics of N2 O were investigated in a plasma reactor positioned in front of a vacuum pump. Fourier transform infrared (FTIR) spectroscopy was used for evaluating the destruction and removal efficiency (DRE) and the identification of byproducts. The concentration of NO x (NO and NO2 ) was quantified by using an NO x analyzer. The DRE of N2 O was enhanced by increasing the power or decreasing the N2 O flow rate. A higher pressure yields a higher DRE of N2 O and a lower concentration of NO x in the destroyed N2 O. For understanding this phenomenon, the discharge characteristics were analyzed by using optical emission spectroscopy (OES). The spatial distribution of emission spectra from the discharge in a mixture of N2 O and Ar gases was measured by varying the pressure. The mechanisms underlying the pressure effect on the N2 O DRE and NO x concentration are discussed in terms of the electron density and the concentration of O radicals.